Strategi Penyelesaian Tindak Pidana Penggelapan dalam Jabatan di PT. Asia Prima Packaging - Kawaiko Hana Jovita; Amil Udin; Ulil Albab (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Embezzlement in office is a crime that often occurs in Indonesia, both in government and corporate companies. The crime of embezzlement in this position can be influenced by many factors. One of the embezzlement acts discussed in this research was at PT. Asia Prima Packaging, where one of the company officials who was entrusted with managing the company's finances took advantage of the trust given by the company by embezzling company money and creating fake official travel and goods delivery documents. The aim of this research is to determine the factors that cause criminal acts of embezzlement in office, legal regulations regarding criminal acts of embezzlement in office, and resolve cases of embezzlement in office at PT. Asia Prima Packaging. This research uses normative juridical research methods by relying on literature as the main basis for data collection.